Plasma KIM-1 and interleukin-18 are superior biomarkers for diagnosing and stratifying risk in type 1 acute cardiorenal syndrome - Alredha, Redha Dawud Abd; Farman, Hassan Ali; Haddawi, Krarr Haider (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Acute cardiorenal syndrome (CRS) is a condition in which acute cardiac dysfunction leads to acute kidney injury (AKI), resulting in high morbidity and mortality rates. This study aimed to assess the diagnostic and prognostic value of plasma kidney injury molecule 1 (KIM-1) and interleukin-18 (IL-18) levels in acute CRS compared to acute heart failure (AHF) and healthy controls. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. A case-control study was conducted with 90 participants divided into three groups: control (n=30), AHF (n=30), and acute CRS (n=30). Renal function parameters (serum creatinine, blood urea nitrogen, estimated glomerular filtration rate) and plasma biomarkers (KIM-1, IL-18) were measured. A receiver operating characteristic curve analysis was used to evaluate diagnostic performance and logistic regression was used to identify predictors of disease outcomes. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. Plasma KIM-1 and IL-18 levels were significantly higher in the acute CRS group than in the AHF and control groups. KIM-1 demonstrated superior diagnostic accuracy (the area under the curve (AUC)=1.000) with 100% sensitivity and specificity, while IL-18 also performed well (AUC=0.96, sensitivity=96%, specificity=97%). ROC analysis identified plasma KIM-1 and IL-18 cut-off values of >72.78 pg/mL and >254.8 pg/mL, respectively, which may be used as thresholds for early diagnosis and risk stratification. Logistic regression analysis revealed that plasma KIM-1 was a significant predictor of adverse outcomes (OR=3.5, 95% CI 1.50–8.49, p=0.003), while IL-18 also contributed to risk stratification (OR=1.06, 95% CI 1.04–1.125, p=0.03). These adverse outcomes included progression to kidney disease. However, these findings require validation in an independent cohort to confirm reproducibility and generalizability. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. KIM-1 and IL-18 are highly effective biomarkers for diagnosing and stratifying the risk of acute CRS, outperforming traditional markers of renal function. Their clinical integration could enable early detection and personalized treatment, thus improving patient outcomes. However, more studies with larger cohorts, serial measurements, and independent validation are warranted.